2011
DOI: 10.3747/pdi.2010.00012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Drain Volume/Fill Volume Ratio and Clinical Outcomes Associated with Overfill Complaints in Peritoneal Dialysis Patients

Abstract: Our analysis of reports from the MAUDE database suggests an association between DV/FV and clinical severity of the reported overfill event, as well as significant patient-to-patient variability with respect to intraperitoneal volume tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…As with all other considerations with regard to PD prescription, clinicians must consider individual patient tolerance to a specific fill volume. While abdominal compliance and tolerance to larger fill volumes is greater when patients are in the supine position, individual body size, habitus, and comorbidities may increase intraperitoneal pressures to undesirable levels, potentially compromising patient safety, particularly after ultrafiltrate is added to the dwell volume (40,41). If nothing else, demonstration of extremes of PD prescription, such as 3-L fill volumes that would be needed to achieve adequacy for patients with < 2mL/min of residual renal urea clearance, higher V urea , and slower membrane transport function, should help highlight for prescribers when it might be appropriate to consider transfer to another dialysis modality, particularly if APD is not an option.…”
Section: Resultsmentioning
confidence: 99%
“…As with all other considerations with regard to PD prescription, clinicians must consider individual patient tolerance to a specific fill volume. While abdominal compliance and tolerance to larger fill volumes is greater when patients are in the supine position, individual body size, habitus, and comorbidities may increase intraperitoneal pressures to undesirable levels, potentially compromising patient safety, particularly after ultrafiltrate is added to the dwell volume (40,41). If nothing else, demonstration of extremes of PD prescription, such as 3-L fill volumes that would be needed to achieve adequacy for patients with < 2mL/min of residual renal urea clearance, higher V urea , and slower membrane transport function, should help highlight for prescribers when it might be appropriate to consider transfer to another dialysis modality, particularly if APD is not an option.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Davis et al (30) reported that insufficient drain was associated with 88% of the increased intraperitoneal volume cases they analyzed. Their finding suggests that potential causes of increased V R should be explored by the attending clinical team in situations in which UF with icodextrin is considerably less than predicted.…”
Section: Discussionmentioning
confidence: 99%
“…However, many events where the DV/FV was high caused very minor symptoms and the variability of the relationship of DV/FV with symptoms was noted. Over 80% of suspected significant overfill events were related to insufficient drains while much smaller numbers were due to excess infusion, device malfunction or excess ultrafiltration (1).…”
mentioning
confidence: 99%
“…A "PubMed" search reveals no articles about PD with 'drain pain' in the title and only one addressing 'overfill' in the sense of an excessive intraperitoneal dialysate volume (1). Are these complications both rare?…”
mentioning
confidence: 99%